Pathophysiology of Bone Loss in Patients with Prostate Cancer Receiving Androgen-Deprivation Therapy and Lifestyle Modifications for the Management of Bone Health: A Comprehensive Review - Kim, Tae Jin (Cancers (Basel), 2020)
Androgen-deprivation therapy (ADT) is a systemic therapy administered for the management of advanced prostate cancer (PCa). Although ADT may improve survival, long-term use reduces bone mass density (BMD), posing an increased risk of fracture. Considering the long natural history of PCa, it is essential to preserve bone health and quality-of-life in patients on long-term ADT. As an alternative to pharmacological interventions targeted at preserving BMD, current evidence recommends lifestyle modifications, including individualized exercise and nutritional interventions. Exercise interventions include resistance training, aerobic exercise, and weight-bearing impact exercise, and have shown efficacy in preserving BMD. At the same time, it is important to take into account that PCa is a progressive and debilitating disease in which a substantial proportion of patients on long-term ADT are older individuals who harbor axial bone metastases. Smoking cessation and limited alcohol consumption are commonly recommended lifestyle measures in patients receiving ADT. Contemporary guidelines regarding lifestyle modifications vary by country, organization, and expert opinion. This comprehensive review will provide an evidence-based, updated summary of lifestyle interventions that could be implemented to preserve bone health and maintain quality-of-life throughout the disease course of PCa.